Kontribusi Tasawuf Dalam Mengatasi Permasalahan Manusia Modern - Guefara, Rahmat Lutfi (STAI Denpasar Bali, 2022)
This study aims to discuss the role of Sufism in addressing the problems faced by modern humans. Modernization has brought many challenges, and modern life often highlights uncommendable traits, especially in terms of materialism. One such uncommendable trait is hirsh, which is an excessive desire for material things. To overcome these traits, Sufism is needed. This study uses a qualitative method with a literature review approach, studying various reference books and relevant previous research to obtain a theoretical foundation regarding the issues being studied. The results of the study indicate that Sufism serves as a remedy for the ailments caused by modernization and its negative impacts.